KAJIAN PEMOTONGAN BABIRUSA (Babyrousa babirussa celebensis DENIGER) SEBAGAI SATWA ENDEMIK SULAWESI UTARA PADA BEBERAPA PASAR TRADISIONAL DI KABUPATEN MINAHASA - Kiroh, H.J; Ratulangi, F.S.; Rimbing, S.C.; Wahyuni, I. (Universitas Sam Ratulangi, 2020)
STUDY ON SLAUGHTER ACTIVITY OF BABIRUSA (Babyrousa babirussa celebensis DENIGER) AS THE ENDEMIC FAUNA IN NORTH SULAWESI AT THE SEVERAL TRADITIONAL MARKETS IN MINAHASA REGENCY. Babirusa (Babyrousa babyrussa celebensis D.) is categorized as a valuable germinal plasma and included into protected fauna since sixty years along a go. Therefore, this animal was noted into endangered animals. However, the hunting activities of the local community are occurring in the remote area of Minahasa as indicated by availability of meat trading of this animal. The objective of this study was to evaluate the slaughter activities dealing with meat trading of this endemic fauna on several traditional markets in Minahasa regency. Study was conducted by survey method focusing on hunters, traders and consumers buying meat of this animal on several traditional markets in Minahasa regency. Results showed that meat of Babirusa (Babyrousa babyrussa celebensis D.) were still traded and found on several traditional markets in Minahasa regency indicated by hunter existences of 0 to 25 percents, meat sellers of 8.33 to 50 percents, and fixed meat consumers of 58.33 to 100 percents of this animal. These cases were spreading on the traditional markets around districts of Tondano, Remboken, Kawangkoan, Langowan and Tanawangko. As the conclusion that slaughters and trading activities of the protected Babirusa (Babyrousa babyrussa celebensis D.) were existing recently in the remote areas of Minahasa Regency.Key words: Babirusa (Babyrousa babyrussa celebensis D.), endemic, Â traditional market.